GRAMMATICAL FEATURES OF TRANSLATION - Khudoyberganova Durdona ismail qizi, (Лучшие интеллектуальные исследования, 2023)
Abstract: In the article, one of the changes occurring in the translation process, grammatical change, is discussed. During the reading this article it can be known that, the types of grammatical transformation and the steps of grammatical transformation.